Association of socio-demographic variables and risk of type 2 diabetes using Indian diabetes risk score: a cross-sectional study in urban Mysuru - Ahmed, Mansoor; A. M., Amrutha (International Journal Of Community Medicine And Public Health, 2018)
Background: About 422 million people worldwide have diabetes. India has 69.2 million people living with diabetes out of a population of 1.3 billion (8.7%) as per the 2015 data. Of these, it remained undiagnosed in more than 36 million people. Early identification of at-risk individuals and appropriate lifestyle intervention would help in preventing or postponing the onset of diabetes mellitus. Present study aimed to study the association of IDRS components with socio demographic and anthropometric variables among adults in urban area of Mysore. Methods: A community-based cross sectional study was conducted in the urban areas of the field practice area of Mysore Medical College and Research Institute. The study was conducted between March and July 2015. Using the estimation set up technique for proportion, the sample size was calculated to be 872 rounded off to 900, with level of significance of 5% and precision of 10%. Risk level for diabetes was assessed using Indian Diabetic Risk Score (IDRS) and sociodemographic and anthropometric factors were assessed through a semi structured pretested questionnaire. Results: Of 900 participants, 197 (21.9%) had a high risk score (IDRS ≥60), the majority of participants (383; 42.5%) were in the moderate-risk category (IDRS 30–50). There was statistically significant difference between type of family and different risk categories under age component of IDRS (p<0.0005). Statistical significance was observed for marital status and SES among different age groups. Association was found significant between family history of diabetes component of IDRS and gender. There was also statistically significant difference between SES and different risk categories under family history of diabetes component of IDRS (p<0.0005). Conclusions: IDRS should be used routinely in community-based screening to find out high risk category of population for diabetes.